2019
DOI: 10.1017/s0305004119000100
|View full text |Cite
|
Sign up to set email alerts
|

Chebyshev’s bias for analyticL-functions

Abstract: AbstractWe discuss the generalizations of the concept of Chebyshev’s bias from two perspectives. First, we give a general framework for the study of prime number races and Chebyshev’s bias attached to general L-functions satisfying natural analytic hypotheses. This extends the cases previously considered by several authors and involving, among others, Dirichlet L-functions and Hasse–Weil L-function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…elements of {γ ≥ 0 : L( 1 2 + iγ, χ) = 0} that are linearly independent of all the other elements of Z(q)). This condition has been further weakened in [Dev19] in the case of a prime number race between two contestants (D = 1). In this paper, we extend the weakening of LI for the weak inclusiveness of prime number races with any fixed number of contestants as a corollary of our main theorem (Corollary 2).…”
Section: Prime Number Racesmentioning
confidence: 99%
See 1 more Smart Citation
“…elements of {γ ≥ 0 : L( 1 2 + iγ, χ) = 0} that are linearly independent of all the other elements of Z(q)). This condition has been further weakened in [Dev19] in the case of a prime number race between two contestants (D = 1). In this paper, we extend the weakening of LI for the weak inclusiveness of prime number races with any fixed number of contestants as a corollary of our main theorem (Corollary 2).…”
Section: Prime Number Racesmentioning
confidence: 99%
“…The existence of the limiting logarithmic distribution of an almost-periodic function F with a finite number of terms, as in Theorem 1, is a consequence of the Kronecker-Weyl Equidistribution Theorem as in [Hum12,Lem. 4.3] (see also [Dev19,Lem. 4.8]).…”
Section: Prime Number Racesmentioning
confidence: 99%
“…Let us now explain how this relates to biases and the random vectors X k,N puq defined above. We adapt classical arguments [RS94,MN17,Dev19] to the function field setting, as in [Cha08,DM18], to show: Theorem 1.14 (Limiting distribution, expected value). The random vector X k,N puq admits a compactly supported limiting distribution as N Ñ 8 with κ ă N {2 fixed.…”
Section: F P (Fixed)mentioning
confidence: 99%
“…Remark 1.18. Concerning the stronger properties of Theorem 1.15 (absolute continuity, symmetry), Devin [Dev19] and Martin-Ng [MN17] have shown that they hold under weaker conditions than full linear independence. However, we cannot exploit these here since their statements always involve all the roots/eigenvalues, while results obtained from the large sieve will be limited to a small subset.…”
Section: F P (Fixed)mentioning
confidence: 99%
“…The literature on this question is rich, and much progress has been made in the recent years. We mention the works [Lit1, KT,Kac2,Pu,RbS,FM,La1] on the Shanks-Rényi problem, as well as generalizations over number fields [Maz,Sa1,Fi2,De,FoS,DGK,LOS,Me] and over function fields [Cha, CI, DM, CFJ]. For an exhaustive list of the numerous papers on the subject, see [GM, MS, M+].…”
mentioning
confidence: 99%